2018
DOI: 10.1002/ppsc.201800359
|View full text |Cite
|
Sign up to set email alerts
|

Structure Analysis of Solid Lipid Nanoparticles for Drug Delivery: A Combined USANS/SANS Study

Abstract: Suspensions of solid lipid nanoparticles (SLNs) stabilized with emulsifiers have been extensively investigated (since the 1990s) as drug carriers, although details of their ultrastructure are poorly defined. Previously, a novel microwave‐assisted microemulsion‐based technique to prepare SLNs was reported. To understand the detailed internal structure of these SLNs, ultra‐small angle neutron scattering (USANS) and small angle neutron scattering (SANS) experiments are conducted on suspensions of hydrogenated ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Figure shows the variation in the total measured scattering with the scattering vector ( Q ) for the SLNs diluted to a final concentration of 0.8 wt% TPN and 2 wt% C 18:1 E 10 in D 2 O. Analysis of the SANS data showed that the SLNs were not spherical, but instead were oblate, as the major and minor axis are different lengths (see the Supporting Information), as has been previously reported from SANS data of steric acid and Tween20 SLNs . In the context of the present study, spherical SLN are generally associated with the α‐form polymorph while the β‐form typically corresponds to platelet shaped SLN.…”
Section: Resultssupporting
confidence: 80%
“…Figure shows the variation in the total measured scattering with the scattering vector ( Q ) for the SLNs diluted to a final concentration of 0.8 wt% TPN and 2 wt% C 18:1 E 10 in D 2 O. Analysis of the SANS data showed that the SLNs were not spherical, but instead were oblate, as the major and minor axis are different lengths (see the Supporting Information), as has been previously reported from SANS data of steric acid and Tween20 SLNs . In the context of the present study, spherical SLN are generally associated with the α‐form polymorph while the β‐form typically corresponds to platelet shaped SLN.…”
Section: Resultssupporting
confidence: 80%
“…When firstly developed, SLN were presented as tiny and spherical particles, made of solid lipids at room temperature, that may be thought as perfect crystal lipid matrices, able to accommodate a drug or other molecules between fatty acid chains (Puri et al, 2009). Nowadays, however, it is known that this is not necessarily true in all cases, since disc-like shape or flat ellipsoidal geometry have also been described (Mazuryk et al, 2016;Shah et al, 2019). Moreover, the loaded drug may be attached mostly to the carrier matrix surface instead of being embedded into the solid core (Pink et al, 2019;Shah et al, 2019).…”
Section: The Tiny Big Universe Of Lipid Nanoparticlesmentioning
confidence: 99%
“…Nowadays, however, it is known that this is not necessarily true in all cases, since disc-like shape or flat ellipsoidal geometry have also been described (Mazuryk et al, 2016;Shah et al, 2019). Moreover, the loaded drug may be attached mostly to the carrier matrix surface instead of being embedded into the solid core (Pink et al, 2019;Shah et al, 2019).…”
Section: The Tiny Big Universe Of Lipid Nanoparticlesmentioning
confidence: 99%
“…1b-d). 29,30 This analysis gives insight to the shape and size of particles based on the Porod exponent (d), dimensionality (s), and radius of gyration (Rg). Fits to HA-CPNs yielded d = 4.2 ± 0.02 and s = 0.02 ± 0.06, which strongly correlates to a hard sphere with a smooth surface (d = 4 and s = 0).…”
Section: Resultsmentioning
confidence: 99%